Study and analysis on hydrocarbon bioremediation potential of different fungal genera - Mohd Farith, Kota (Universiti Malaysia Sarawak (UNIMAS), 2013)
One of the major environmental problems today is hydrocarbon contamination from the activities related to the petrochemical industry. Bioremediation is a promising technology for the treatment of these contaminated sites as it is cost effective and lead to complete mineralization. This research attempts to study the potential of different fungal genera for potential use in bioremediation of hydrocarbon. Aspergillus flavus UMAS HDF8, Aspergillus versicolor UMAS HDF6, Bionectria ochroleuca UMAS BHDF7, Penicilium chermisinum UMAS HDF2 and Trichoderma virens UMAS HSF7 were employed for the bioremediation purposes. Screening of fungal strain sensitivity towards hydrocarbons was first conducted. In order to enhance the growth of fungi on hydrocarbon contaminated soil, the suitable bulking agent was selected. The hydrocarbon degradation trial was conducted for a period of six weeks, followed by post-treatment tests. All of the fungal strains showed high tolerance towards hydrocarbon. Sago waste (sago hampas) is found as the most suitable bulking agent as all of the fungal test strains capable to growing on it. A significant difference was found in the ability of B. ochroleuca UMAS BHDF7 to degrade hydrocarbon. B. ochroleuca UMAS BHDF7 was able to degrade more than 80% of the C12 to C28, with 100% degradation of C12 and C28.